Predicted indirectly recognizable HLA epitopes scores and clinical outcomes after haploidentical stem cell transplantation in pediatric patients with relapsed neuroblastoma - Seo, Eun Seop; Jeong, In Hwa; Ju, Hee Young; Hyun, Ju Kyung; Lee, Ji Won; Yoo, Keon Hee; Heo, Won Young; Sung, Ki Woong; Cho, Hee Won; Kang, Eun-Suk (Frontiers in Immunology, 2025)
IntroductionThe Predicted Indirectly ReCognizable HLA Epitopes (PIRCHE) model is a recently developed algorithm that predicts indirect T-cell recognition by calculating the number of such epitopes in donor-recipient pairs.MethodsIn this study, the clinical significance of PIRCHE was evaluated in pediatric patients with relapsed/progressed neuroblastoma undergoing haploidentical stem cell transplantation (haplo-SCT).ResultsA higher PIRCHE-I score was associated with faster platelet recovery (P = 0.007) and lower incidence of hemorrhagic cystitis (13% vs. 41%, P = 0.028) and invasive fungal infections (0% vs. 18%, P = 0.045). Additionally, a higher PIRCHE-I score was significantly associated with better overall survival (OS) (HR 0.57, 95% CI 0.34-0.97, P = 0.038). A higher PIRCHE-II score was associated with better OS (HR 0.57, 95% CI 0.34-0.94, P = 0.028) and reduced progression (HR 0.48, 95% CI 0.30-0.77, P = 0.002). When combined, the PIRCHE-I and PIRCHE-II scores demonstrated an even stronger association with improved OS (HR 0.35, 95% CI 0.15-0.82, P = 0.016). Multivariable analysis confirmed that a higher combined PIRCHE-I and PIRCHE-II score was independently associated with improved OS (combined PIRCHE score HR 0.22, 95% CI 0.06-0.79, P = 0.021), and a higher PIRCHE-II score was significantly associated with reduced progression (HR 0.42, 95% CI 0.25-0.70, P < 0.001).ConclusionIn conclusion, higher PIRCHE-I and PIRCHE-II scores are linked to better survival outcomes and reduced complications in pediatric haplo-SCT neuroblastoma patients. Incorporating PIRCHE scores into donor selection is expected to optimize transplant outcomes.